2011
DOI: 10.1007/s10461-011-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Other Risk Factors for Unprotected Sex: Results from an Event-Based Study of Homeless Youth

Abstract: This study used an event-based approach to understand condom use in a probability sample of 309 homeless youth recruited from service and street sites in Los Angeles County. Condom use was significantly less likely when hard drug use preceded sex, the relationship was serious, the partners talked about “pulling out”, or sex occurred in a non-private place (and marginally less likely when heavier drinking preceded sex, or the partnership was monogamous or abusive). Condom use was significantly more likely when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 36 publications
5
73
1
3
Order By: Relevance
“…In other words, living on the streets and insecurity related to having no housing 7,11,20,28 are per se factors that bring about situations of greater exposure to HIV such as violence and no access to services. 14,26,29 These same particularities may largely explain the study fi nding that young, female and homeless individuals engaging in homosexual sex are more vulnerable to HIV infection. We found that, among those engaging in homosexual sex, at least one out of 10 are living with HIV.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, living on the streets and insecurity related to having no housing 7,11,20,28 are per se factors that bring about situations of greater exposure to HIV such as violence and no access to services. 14,26,29 These same particularities may largely explain the study fi nding that young, female and homeless individuals engaging in homosexual sex are more vulnerable to HIV infection. We found that, among those engaging in homosexual sex, at least one out of 10 are living with HIV.…”
Section: Discussionmentioning
confidence: 95%
“…As a result, these groups more frequently report sexual abuse, violence, discrimination, drug and alcohol use, and exchange of sex for money and favors. 6,9,14,21,22,26 Among homosexuals, homophobia has been identifi ed as the main factor driving them onto streets. 4.19 A qualitative study conducted in Los Angeles 21 showed that women's choice to use condoms is strongly affected by their emotional involvement and trust in their partner, and that sex occur due to various reasons including sexual abuse and need for affective involvement.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Once youth become homeless, they are at increased risk for multiple adverse health outcomes, notably sexual health related, such as sexually transmitted diseases (STDs) and human immunodeficiency virus (HIV). 5,6 Compared with housed youth, homeless youth are more likely to experience teen dating violence, teen pregnancy, and poor mental health. 7 Homeless youth are also more likely to engage in high-risk sexual behaviors, such as unprotected intercourse, multiple sexual partners, and drug and alcohol use, putting them at increased risk for acquiring STDs.…”
mentioning
confidence: 99%
“…Studies have explored behavioral risk factors associated with STD acquisition in homeless youth, 6,12 and there are reviews specific to HIV. 13,14 To date, however, no reviews have focused exclusively on STD prevalence or incidence among homeless youth in the United States.…”
mentioning
confidence: 99%
“…Il est également montré que la consommation de drogues chez les jeunes en situation de rue augmente les risques de contracter le VIH et l'hépatite C (Roy et al, 2009 ;Roy et al, 2001), principalement chez ceux qui consomment des substances par injection (Kissin et al, 2007 ;Roy et al, 2000). La consommation de drogues serait aussi associée à des partenaires sexuels multiples (El Khouri et Gagnon, 2011 ;Gleghorn, Marx, Vittinghoff & Katz, 1998 ;Nyamathi et al, 2010) et à une utilisation déficiente de moyens de contraception chez les jeunes en situation de rue (Bailey, Camlin & Ennett, 1998 ;Haley, Denis & Roy, 2005 ;Hathazi, Lankenau, Sanders & Jackson Bloom, 2009 ;Tucker et al, 2012). D'ailleurs, certaines jeunes femmes interrogées affirment avoir l'impression que leur consommation de drogues diminuerait leur fertilité, ce qui rendrait inutile, à leurs yeux, le recours à des moyens contraceptifs (Haley et al, 2005).…”
Section: Introductionunclassified